The ABC-CLIO companion to the disability rights movement - Pelka, Fred, 1954- (ABC-CLIO companions to key issues in American history and life., 1997)
Now students, general readers, advocates, rehabilitation professionals, and others seeking to learn more about the history and progress of the disability rights movement can turn to a valuable new reference book, The ABC-CLIO Companion to the Disability Rights Movement. The book is designed as a general introduction to the many varied influences on the growth of this movement, including notable individuals, some of whom will be familiar to general readers, while others remain virtually unknown outside of the communities they have affected. Here, through fascinating biographical narratives, their contributions are highlighted.